(untitled) (Al-Aasar, 2026)
Abu al-Hasan Saʿid ibn Masʿadah al-Akhfash al-Awsat occupies a significant position in the history of Arabic linguistic and literary scholarship. Although primarily known as a distinguished grammarian of the Basran school, his contributions to Arabic prosody (ʿIlm al-ʿArūḍ) represent an important development in the evolution of classical Arabic literary theory. While al-Khalīl ibn Aḥmad al-Farāhīdī established the foundations of Arabic prosody, al-Akhfash played a crucial role in interpreting, refining, and extending the Khalilian system. His most influential achievement was the identification of Baḥr al-Mutadārik, which later became recognized as the sixteenth Arabic poetic meter. This study examines al-Akhfash’s prosodic thought through historical, analytical, structural, and epistemological perspectives. It explores his intellectual background, his relationship with the Basran grammatical tradition, and his engagement with the theoretical principles of al-Khalīl’s prosodic framework. Particular attention is given to his analysis of the prosodic circles and his derivation of Baḥr al-Mutadārik from the Dāʾirah al-Muttafiqah. Through a critical examination of classical Arabic poetic texts, the study demonstrates that al-Akhfash did not introduce an arbitrary metrical innovation; rather, he identified rhythmic possibilities already embedded within the Arabic poetic tradition. The research also evaluates the scholarly debates surrounding the acceptance of Baḥr al-Mutadārik and examines the objections raised by conservative prosodists. Drawing upon the philosophy of knowledge, the study argues that al-Akhfash’s methodology reflects a productive balance between tradition and innovation. His work illustrates how intellectual systems evolve through critical inquiry and scholarly ijtihād rather than mere imitation. Furthermore, employing selected concepts from modern Structuralism, the research contends that Baḥr al-Mutadārik emerged from latent structural possibilities inherent within the Khalilian system rather than constituting an entirely new invention. The study also traces the influence of al-Akhfash’s prosodic ideas on later Arabic, Persian, and Urdu poetic traditions, where Baḥr al-Mutadārik gained considerable popularity. It concludes that al-Akhfash al-Awsat was not merely a transmitter of inherited knowledge but an original and critical thinker who expanded the horizons of Arabic prosodic theory. His legacy demonstrates the dynamic nature of intellectual traditions and their capacity for renewal through scholarly engagement and creative interpretation.